Aardman Classics - Park, Nick; Fell, Sam; Kossmehl, Boris; Lord, Peter; Sproxton, David; Goleszowski, Richard; Newitt, Jeff; Box, Steve; Peake, Peter (Momentum Pictures, 2000)
Sit back and enjoy all the fun of the ultimate animated colection from the creators of Morph, Wallace and Gromit, and Chicken Run. Together at last, on one DVD, is the complete collection of award winning short films from the world's best loved and most successful model animation studio - Aardman. This includes Nick Park's Oscar-winning favourite "Creature Comforts", the complete Heat Electric ad campaign it inspired, anarchic fun with Pib and Pog, medieval tales from BAFTA-winning Wat's Pig as well as 22 other classic films, there's no doubt this collection has something for everyone. [Cover]